Efficacy of Grass Carp (Ctenopharyngodon idella) in Controlling Aquatic Weeds in Rural Farm Ponds: A Field Demonstration Study - Alagappan, M.; Sendur, Kumaran S. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during November, 2023 to March, 2024 in the farmers’ farm ponds at Kalayarkoil and Ilayangudi villages in Sivaganga district, Tamil Nadu, India to evaluate the efficacy of grass carp (Ctenopharyngodon idella) in controlling aquatic weeds and enhancing pond productivity under rainfed farming conditions. A total of five farm ponds of 0.1ha each were selected and uniformly stocked with 500 Grass carp fingerlings without supplemental feeding. Over a 120-day culture period, a significant reduction in weed biomass was observed, with a mean decrease of 79.8%, particularly in dominant species such as Hydrilla verticillata and Najas minor. Concurrently, grass carp showed robust growth performance with average daily weight gains of 2.53–3.07 g day-1 and a mean final weight of 427.6 g, achieving a mean survival rate of 89.8%. Economic analysis revealed a benefit-cost ratio (BCR) ranging from 2.9 to 3.5, factoring in both weed control savings and fish harvest revenue. Farmer feedback indicated high satisfaction levels (mean rating 4.4 out of 5), with 100% of participants willing to restock in the following season. Perceived benefits included reduced labour, improved water quality, and enhanced biodiversity. Minor adoption barriers, such as fingerling availability and transport costs, were noted. The study validates grass carp as a sustainable, cost-effective, and farmer-friendly solution for managing aquatic weeds in farm ponds, with strong potential for scaling under participatory extension programs.